what is the solution of the equation 8 +6x= 14 solving for x?

21 answers

To solve the equation 8 + 6x = 14 for x, we can start by subtracting 8 from both sides of the equation to isolate the term with x:

8 + 6x - 8 = 14 - 8
6x = 6

Next, divide both sides of the equation by 6 to solve for x:

6x/6 = 6/6
x = 1

Therefore, the solution to the equation 8 + 6x = 14 is x = 1.
what is the solution of the equation x/3-9=6 solving for x?
To solve the equation x/3 - 9 = 6 for x, follow these steps:

Step 1: Start by adding 9 to both sides of the equation to isolate the term with x:
x/3 - 9 + 9 = 6 + 9
This simplifies to:
x/3 = 15

Step 2: Multiply both sides of the equation by 3 to get rid of the fraction:
(x/3) * 3 = 15 * 3
This simplifies to:
x = 45

Therefore, the solution to the equation x/3 - 9 = 6, solving for x, is x = 45.
randall needs to solve the equation 5x+8=63. his first mathmatical operation used to isolate x is subtration. which value will he apply it to
To isolate x in the equation 5x + 8 = 63, Randall will apply subtraction to the term with the constant 8.

He will subtract 8 from both sides of the equation.
9x - 6= 12 by what value does each side need to be divided
To solve the equation 9x - 6 = 12, each side needs to be divided by the coefficient of x, which is 9.

Dividing both sides by 9, we get:

(9x - 6) / 9 = 12 / 9

Simplifying, we have:

x - (6/9) = 4/3

The equation can be further simplified to:

x - 2/3 = 4/3

Therefore, each side needs to be divided by 9 in order to isolate x.
beejal is solving the equation y/7-3=39
as a first step , he starts by adding __ to bothe sides of the equation, then continues by multiplying by __ on each side
To solve the equation y/7 - 3 = 39, Beejal can start by adding 3 to both sides of the equation to isolate the term with y.

y/7 - 3 + 3 = 39 + 3

This simplifies to:

y/7 = 42

The next step Beejal can take is multiplying both sides of the equation by 7 to solve for y.

(y/7) * 7 = 42 * 7

This simplifies to:

y = 294

Therefore, Beejal added 3 to both sides and then multiplied by 7 on each side to solve the equation.
identify the first step in solving this equation for x:-3=x/4+2
The first step in solving the equation -3 = x/4 + 2 for x is to subtract 2 from both sides of the equation.

Doing so, we have:

-3 - 2 = x/4 + 2 - 2

This simplifies to:

-5 = x/4

Therefore, the first step is to subtract 2 from both sides of the equation.
10z-6=24 solving for z what is the answer
To solve the equation 10z - 6 = 24 for z, follow these steps:

Step 1: Start by adding 6 to both sides of the equation to isolate the term with z:
10z - 6 + 6 = 24 + 6
This simplifies to:
10z = 30

Step 2: Divide both sides of the equation by 10 to solve for z:
10z / 10 = 30 / 10
This simplifies to:
z = 3

Therefore, the solution to the equation 10z - 6 = 24, solving for z, is z = 3.
jonny is solving this equation for n: 8 +3n=20. his first step is to subtract 8 from both sides of the equation. why
Jonny subtracts 8 from both sides of the equation, 8 + 3n = 20, to isolate the term with n.

By subtracting 8 from both sides, he can eliminate the constant term on one side of the equation and move the 3n term to be by itself on the left-hand side.

This step allows him to simplify the equation and make it easier to solve for n by dividing both sides by the coefficient of n, which is 3.
samule is solving and equation for y his first step is to add 7 to both sides. which equation is he solving

2y-7=15
2y-15=7
2y+15=7
2y+7=15
Samuel is solving the equation 2y - 7 = 15.
His first step is to add 7 to both sides of the equation.
kelia is solving and eqation for x. her second step is to multiply both sides of the equation by 4.
To continue the process of solving the equation, it would be helpful to know the original equation Kelia is working on. Please provide the original equation so that I can assist you better.
kelia is solving and eqation for x. her second step is to multiply both sides of the equation by 4.
4+6x=1
6+4x=1
4+x/6=1
6+x/4=1
If Kelia's second step is to multiply both sides of the equation by 4, and the original equation is 4 + 6x = 1, then the second equation would be:

4(4 + 6x) = 4(1)

This simplifies to:
16 + 24x = 4

Therefore, the equation after multiplying both sides by 4 would be 16 + 24x = 4.
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 7 answers
more similar questions